Augmented Reality Media and Teacher Teaching Skills on Early Childhood Learning Outcomes: The Mediating Role of Motivation - Angri Lismayani; Muh. Isbar Pratama (Indonesian Technology and Education Journal, 2026)
The motivational mechanisms through which Augmented Reality (AR) media and teacher teaching skills jointly influence early childhood learning outcomes remain empirically underspecified, particularly within the PAUD Indonesian context where contextually grounded evidence is scarce. This study examines the direct and indirect effects of AR media and teacher teaching skills on learning outcomes, with motivation specified as a formal mediating construct. A quantitative cross-sectional design was employed with 205 certified PAUD teachers drawn from various regions in South Sulawesi, Indonesia, recruited through purposive sampling. Data were analysed using PLS-SEM in SmartPLS 4.0, with significance assessed via bootstrapping across 5,000 subsamples. The measurement model demonstrated acceptable reliability (Cronbach's α: 0.815–0.836), convergent validity (AVE: 0.576–0.604), and discriminant validity confirmed through HTMT ratios ranging from 0.723 to 0.822, each below the 0.90 threshold. AR media was significantly associated with both motivation (β = 0.438, p < 0.001) and learning outcomes (β = 0.329, p = 0.001). Teacher teaching skills significantly predicted motivation (β = 0.483, p < 0.001) and learning outcomes (β = 0.440, p < 0.001). Motivation was the strongest direct predictor of learning outcomes (β = 0.539, p < 0.001), partially mediating both the AR learning outcomes and teacher skills–learning outcomes relationships. These findings suggest that instructional quality whether technological or human must first activate motivational engagement to produce measurable learning outcomes. PAUD institutions are encouraged to develop teacher competency and AR infrastructure concurrently, with motivational quality as a key process indicator of instructional effectiveness.